Perancangan Sistem Informasi Data Mining Dengan Algoritma Apriori Untuk Penentuan Layout Produk Pada PT. Metro Makmur Nusantara - So, Olivia (STMIK TIME, 2015)
Nowadays, PT. Metro Makmur Nusantara (Metro Supermarket) is one of developing retail businesses in Medan which oriented on food and nonfood products. PT. Metro Makmur Nusantara has used Magic Retail Information System (MARIS) system information to store and manage all sales data in company. However, the applied system canât provide the decision-making information, such as analyzing the customer shopping cart (market basket analysis).For providing the information, method of data mining can be applied. Data mining is the extraction of important information or interesting patterns from large database that had been unknown, yet potentially useful information. Apriori algorithm is data retrieval algorithms with associative rules to determine the associative relationship of the items combination. The association rule is done through the mechanism of calculating support and confidence of an item set.The result of this research is a data mining application that helps the company management to find products which often purchased together in sales transaction, so the products layout can be arranged. This also can improve the efficiency of customerâs time in finding and buying products in the supermarket.